AB0650 Behcet Disease Frequency Among People with Visual Loss. (9th June 2015) - Uyaroglu, O.; Erden, A.; Tatar, O.; Babaoglu, H.; Vahabov, C.; Karadag, O.; Kilic, L.; Akdogan, A.; Bilgen, S.A.; Kiraz, S.; Ertenli, I.; Kalyoncu, U.
Abstract : Background: Ocular involvement is one of the major reason of disability for Behcet disease (BD). BD may be a cause of acquiered blindness particularly among young adult population. Objectives: The objective of this study was to assess prevalence of severe visual loss with BD among blind population. Methods: Demographic data of blind people was recorded and followed by Ankara metropolitan municipality education and technology center. There were 675 blind people at these center. Telephone numbers were not found at 131 peoples and we also did not reach 250 peoples by phone. At the end, medical history was took from 294 peoples. Participants were searched by standard questionnaire for BD. We also searched to cause of blindness either acquired or congenital. If patients had BD or suspicious BD, they were recalled for future investigation for BD by a rheumatology and ophtalmology physician. Patients with BD were assessed for disease characteristics, time of visual impairment. Results: Overall, 213 of 294 (72.4%) peoples were male. One hundred nine of 294 (37.1%) peoples had acquired blindness. Six of those 109 (5.5%) patients had BD. Five of 6 patients already had BD, however, 1 of 6 patients did not known their diagnosis. All of BD were male sex, median age was 38.6 years old (range 24-64 years).The median age for diagnosis was 20 years old (range 14-35 years) and the median duration from diagnosis to visual loss was 2.5 years (range 1- 11 years). All patients with BD had recurrent oral aphtous ulcer and ocular involvement. Other diseease characteristics were genital ulcers (83%), skin involvement (67%), arthritis (50%), arthralgia (66%), neurological involvement (17%). None of the patients had deep venous thrombosis. Uveitis location were known at 3 patients, one had both anterior and posterior uveitis, 2 patients had only posterior uveitis. Conclusions: BD is still one of the cause of acquired visual impairment in Turkey. In a Japan study at 1965, on the other hand before immunosuppressive treatment period, BD was the 12% of cause of acquired blindness (1). Today, immunosuppressive treatments use in routine practice, and frequency of BD among visual loss population looks tendency of decrease. However BD still seems to be important cause of acquired visual loss, particularly prevalant country such as Turkey. References: Shimizu T, Tanaka I, Ogino K. Current status of Behcet's disease in Japan. Igaku no Ayumt 75:332-341, 1970 Disclosure of Interest: None declared